MASB Exposure Draft 74 Reduced disclosure requirements - Lembaga Piawaian Perakaunan Malaysia (Kuala Lumpur : Lembaga Piawaian Perakaunan Malaysia, 2011)
This Exposure Draft (ED) is issued by the Malaysian Accounting Standards Board for comment only. The recommendations in the Exposure Draft may be modified in the light of comments received before being issued in the form of Amendments to Financial Reporting Standards arising from Reduced Disclosure Requirements.
Keywords: Financial statements -- Standards -- Malaysia; Accounting -- Standards -- Malaysia; Property -- Accounting -- Malaysia